Overexpression of a Neuronal Type Adenylyl Cyclase (Type 8) in Sinoatrial Node Markedly Impacts Heart Rate and Rhythm - Moen, Jack M.; Matt, Michael G.; Ramirez, Christopher; Tarasov, Kirill V.; Chakir, Khalid; Tarasova, Yelena S.; Lukyanenko, Yevgeniya; Tsutsui, Kenta; Monfredi, Oliver; Morrell, Christopher H.; Tagirova, Syevda; Yaniv, Yael; et al. (Frontiers in Neuroscience, 2019)
Heart rate (HR) and HR variability (HRV), predictors of over-all organism health, are widely believed to be driven by autonomic input to the sinoatrial node (SAN), with sympathetic input increasing HR and reducing HRV. However, variability in spontaneous beating intervals in isolated SAN tissue and single SAN cells, devoid of autonomic neural input, suggests that clocks intrinsic to SAN cells may also contribute to HR and HRV in vivo. We assessed contributions of both intrinsic and autonomic neuronal input mechanisms of SAN cell function on HR and HRV via in vivo, telemetric EKG recordings. This was done in both Wild Type (WT) mice, and those in which adenylyl cyclase type 8 (ADCY8), a main driver of intrinsic cAMP-PKA-Ca2+ mediated pacemaker function, was overexpressed exclusively in the heart (TGAC8). We hypothesized that TGAC8 mice would: (1) manifest a more coherent pattern of HRV in vivo, i.e. a reduced HRV driven by mechanisms intrinsic to SAN cells, and less so to modulation by autonomic input and (2) utilize unique adaptations to limit sympathetic input to a heart with high levels of intrinsic cAMP-Ca2+ signaling. Increased adenylyl cyclase (AC) activity in TGAC8 SAN tissue was accompanied by a marked increase in HR and a concurrent marked reduction in HRV, both in the absence or presence of dual autonomic blockade. The marked increase in intrinsic HR and coherence of HRV in TGAC8 mice occurred in the context of: (1) reduced HR and HRV responses to β-adrenergic receptor (β-AR) stimulation; (2) increased transcription of genes and expression of proteins (β-Arrestin, G Protein-Coupled Receptor Kinase 5 (GRK5) and Clathrin Adaptor Protein (Dab2) that desensitize β-AR signaling within SAN tissue, (3) reduced transcripts or protein levels of enzymes (Dopamine Beta-Hydorxylase (DBH) and Phenylethanolamine N-Methyltransferase (PNMT) required for catecholamine production in intrinsic cardiac adrenergic cells; and (4) substantially reduced plasma catecholamine levels. Thus, mechanisms driven by cAMP-PKA-Ca2+ signaling intrinsic to SAN cells underlie the marked coherence of TGAC8 mice HRV. Adaptations to limit additional activation of AC signaling, via decreased neuronal sympathetic input, are utilized to ensure the hearts survival and prevent Ca2+ overload.